Comparative Transcriptome Analysis of Actinidia arguta Fruits Reveals the Involvement of Various Transcription Factors in Ripening - HUANG, Guohui; QU, Yi; LI, Tong; YUAN, Hui; WANG, Aide; TAN, Dongmei (Horticultural plant journal, 2018)
The fruit of Actinidia arguta is typically climacteric. During ripening, the fruits produce a large amount of ethylene. Although the molecular basis of climacteric fruit ripening has been extensively studied, some aspects such as its transcriptional regulation remain unclear. Here, we compared the transcriptomes of A. arguta fruits collected at commercial harvest (sample d0) and at 6 days after harvest (sample d6) using RNA-seq. A total of 3 659 differentially expressed genes (DEGs) between samples d0 and d6 were detected, of which 2 983 and 1 104 could be functionally annotated with Gene Ontology (GO) and Clusters of Orthologous Groups (COG) pathways. DEGs involved in ethylene biosynthesis and signal transduction were identified, including ACO (c79627), ERF061 (c105131), and ERF6 (c99193). Transcription factors such as ERF, bHLH, NAC, MADS, and MYB were also differentially expressed between samples d0 and d6. Selected DEGs were subjected to further analysis using quantitative reverse transcription-polymerase chain reaction (qRT-PCR), and the results coincided with those of RNA-seq. Our data revealed additional transcription factors that are involved in the regulation of fruit ripening. These results provide useful information for future research on the transcriptional regulation of fruit ripening.